1986
DOI: 10.1007/bf00040126
|View full text |Cite
|
Sign up to set email alerts
|

Production of betalains by suspension cultures of Chenopodium rubrum L.

Abstract: Red-violet cell suspension cultures of Chenopodium rubrum were found to accumulate the betacyanins amaranthin, celosianin and betanin and the betaxanthins vulgaxanthin I and vulgaxanthin II. Under a 16-h daylight regime the cells accumulated 0.3-0.4% betacyanins on a dry mass basis after 2-3 weeks of cultivation on the growth medium. Experiments to define a production medium for betacyanins failed with this habituated line. The accumulation could however be increased up to 1% or 100rag betacyanins/1 by feeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(29 citation statements)
references
References 23 publications
(14 reference statements)
2
26
0
1
Order By: Relevance
“…Regardless of the treatment used, these authors found that the presence of tyrosine in the culture medium led to the lowest values of dry matter. Berlin et al (1986) also found this negative effect in Chenopodium rubrum L. (red goosefoot) cell culture using 15 µM tyrosine. Their results revealed that high amounts of this amino acid might be toxic to cell proliferation and growth of this species.…”
Section: In Vitro Culturing Of a Tenellamentioning
confidence: 81%
See 2 more Smart Citations
“…Regardless of the treatment used, these authors found that the presence of tyrosine in the culture medium led to the lowest values of dry matter. Berlin et al (1986) also found this negative effect in Chenopodium rubrum L. (red goosefoot) cell culture using 15 µM tyrosine. Their results revealed that high amounts of this amino acid might be toxic to cell proliferation and growth of this species.…”
Section: In Vitro Culturing Of a Tenellamentioning
confidence: 81%
“…The increase in betacyanin production due to the elicitor action of tyrosine has been reported. Berlin et al (1986) used 15 µM tyrosine in the culture of Chenopodium rubrum callus tissue and demonstrated an increase in the production of betalains of 50 to 100% after 28 days of culture. Silva et al (2005) found that the production of betalains increased compared to the control in the in vitro culture of A. brasiliana for 45 days in MS medium supplemented with 10 µM tyrosine.…”
Section: In Vitro Culturing Of a Tenellamentioning
confidence: 99%
See 1 more Smart Citation
“…This result was in agreement with Bamberger and Mayer (1960), who reported increased pigment synthesis in plantlets of Amaranthus caudatus in presence of kinetin. It has been demonstrated that betacyanin biosynthesis is also stimulated by white light in Amaranthus tricolor and Chenopodium rubrum (Berlin et al, 1986). Plantlets of A. brasiliana grown in MS with kinetin under white or white + UV-A illumination or MS plus tyrosine under white light, produced more betacyanin than other treatments (Table 2).…”
Section: Discussionmentioning
confidence: 96%
“…In general, AsA scavenges the free radical oxygen species and prevents such injuries as peroxidization of lipids, degradation of pigments and inactivation of enzymes (Shigeoka, 1996). Furthermore, ascorbate and related enzymes can be of particular importance in regulating growth and development in plants (Cordoba and Gonzaez-Reyes, 1994 (Berlin et al, 1986) and Phytolacca americana (Sakuta et al, 1986). (Schroder et al, 1979;Kreuzaler et al, 1983) and carrot (Takeda et al, 1993 …”
Section: Discussionmentioning
confidence: 99%